2018
DOI: 10.1039/c7fd00221a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat treatment atmosphere on the structure and activity of Pt3Sn nanoparticle electrocatalysts: a characterisation case study

Abstract: Comprehensive identification of the phases and atomic configurations of bimetallic nanoparticle catalysts are critical in understanding structure-property relationships in catalysis. However, control of the structure, whilst retaining the same composition, is challenging. Here, the same carbon supported Pt 3 Sn catalyst is annealed under air, Ar and H 2 resulting in variation of the extent of alloying of the two components. The atmosphere-induced extent of alloying is characterised using a variety of methods i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…The formation of such subnanometric Pt-SnOx interfacial structure can explain the absence of Pt-Sn bonding in the EXAFS results, since Pt and Sn are not in the form of conventional PtSn alloy nanoparticles. [32][33][34][35]…”
Section: Determination Of the Pt And Sn Distribution In K-ptsn@mfimentioning
confidence: 99%
“…The formation of such subnanometric Pt-SnOx interfacial structure can explain the absence of Pt-Sn bonding in the EXAFS results, since Pt and Sn are not in the form of conventional PtSn alloy nanoparticles. [32][33][34][35]…”
Section: Determination Of the Pt And Sn Distribution In K-ptsn@mfimentioning
confidence: 99%
“…As shown in Scheme S1, Supporting Information, by virtue of its low‐melting‐point (232 °C) and ease of oxidation, the Sn is easily separated from the PtSn NPs, and further transformed into SnO 2 by the simple but effective process of annealing (at 300 °C) in static air. [ 25 ] The annealing temperature affected the particle size and content of surficial/interfacial oxygen in PtSnO 2 /C, which could further affect their ORR activity. It was found that 300 °C was the optimum annealing temperature (see the Supporting Information for details).…”
Section: Figurementioning
confidence: 99%
“…However, the results must be interpreted with caution as the environment in which the XAS data were acquired can have a significant effect. The well-studied Pt-Sn nanoparticles (Pt as the host metal and Sn as the guest), catalysts for alkane dehydrogenation [23][24][25][26][27][28] and electrocatalysts for CO and alcohol oxidation, 4,8,[29][30][31] may be used as an example. Decreases in the Sn-Pt bond length of 0.03 to 0.15 Å have been reported compared to that of the Pt 3 Sn structure.…”
Section: Introductionmentioning
confidence: 99%